1993
DOI: 10.1016/s0022-5347(17)35998-0
|View full text |Cite
|
Sign up to set email alerts
|

Collagenase Versus Placebo in the Treatment of Peyronie’s Disease: A Double-blind Study

Abstract: We investigated 49 men with Peyronie's disease in a prospectively randomized placebo controlled double-blind study, comparing the effects on plaque size and penile deformity of intralesional purified clostridial collagenase and saline placebo. For the group as a whole, treatment out-performed placebo (p < 0.007). When patients were analyzed with respect to disease severity, those with lesser deformity responded more favorably to treatment. The absolute angular change in patients responding to treatment was sma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
119
1
9

Year Published

1999
1999
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 197 publications
(135 citation statements)
references
References 5 publications
5
119
1
9
Order By: Relevance
“…27 In this study of 49 men, a statistically significant improvement in plaque size was found following collagenase treatment as compared to placebo control. The patients were stratified according to the severity of their disease and a modified Kelami system was used for classification.…”
Section: Intralesional Therapymentioning
confidence: 60%
“…27 In this study of 49 men, a statistically significant improvement in plaque size was found following collagenase treatment as compared to placebo control. The patients were stratified according to the severity of their disease and a modified Kelami system was used for classification.…”
Section: Intralesional Therapymentioning
confidence: 60%
“…46 Initial trials of intra-plaque injection with collagenase have been disappointing. 47 Intralesional injection of either alpha 2A or alpha 2B interferon have also been reported with mixed results. 48,49 Oral tamoxifen has been tested as a therapeutic agent to treat Peyronie's disease.…”
Section: Molecular Mechanisms: Oxidative Damage and The Role Of Free mentioning
confidence: 99%
“…Adverse events occurred in 20 (80%) patients, with edema, penile pain and ecchymosis as the most common. A double-blind, placebocontrolled trial by Gelbard et al 59 in 1993, composed of 49 men, showed a statistically significant improvement in vacuum-induced curvature in the treatment group when compared with placebo; however, maximal improvement ranged from 151 to 201 and was only seen in the patients with curvature of less than 301 and plaques of less than 2 cm in length. Currently, this agent is in a large scale, multicenter, multination, randomized, placebo-controlled trial, 60 which may become the first FDA-approved treatment for PD.…”
Section: Collagenasementioning
confidence: 99%